PENINGKATAN HASIL BELAJAR MAHASISWA AKUNTANSI MELALUI MEDIA PEMBELAJARAN INTERAKTIF GENIALLY - Novitasari, Novitasari; Mahatmyo, Atyanto; Vidyasari, Rahmanita (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The classic learning method using presentation media apparently does not maximize student learning outcomes. Therefore, combining it with more interactive and creative learning media, such as Genially media is necessary. This research aims to improve student learning outcomes in bank accounting learning through Genially interactive learning media. The research methodology used is quantitative descriptive research. It uses classroom experimental research methods with the Kemmis-McTaggart model approach, and the analysis technique uses the N-Gain and Mann-Whitney tests. The results of the research state that the use of genetically interactive learning media is quite effective in improving student learning outcomes in foreign currency current account accounting material. There are differences in student learning outcomes in classes that use Genially interactive learning media (experimental class) and classes that do not use Genially learning media (class control). The experimental class had higher learning outcomes compared to the control class. From this research, Genially media is suitable for use in the learning process because it can help improve student learning outcomes.